Effects of the Co‐occurrence of Anxiety and Attention‐Deficit/Hyperactivity Disorder on Intrinsic Functional Network Centrality among Children with Autism Spectrum Disorder. Issue 7 (10th May 2019) - Wan, Bin; Wang, Zengjian; Jung, Minyoung; Lu, Yanchun; He, Haoqiang; Chen, Qi; Jin, Yu
Abstract : Children with autism spectrum disorder (ASD) present with a high co‐occurrence of anxiety and attention‐deficit/hyperactivity disorder (ADHD). However, it remains unclear how the co‐occurrence of anxiety and ADHD in children with ASD alters whole‐brain functional networks. Here, we aimed to examine anxiety‐ and ADHD‐related brain network centrality in children with ASD separately and their relationships with ASD symptoms. Clinical anxiety and ADHD levels in children with ASD, aged 6–13 years old, were assessed. Participants were categorized into four groups: ASD only ( n = 28), ASD + anxiety ( n = 19), ASD + ADHD ( n = 25), and ASD + both anxiety and ADHD ( n = 28). Subsequently, we compared voxel‐wise network degree centrality (DC) among the four groups. We found that: (a) compared with ASD only, children with ASD + anxiety showed higher DC in the left middle temporal gyrus, right lingual gyrus, and left cuneus, and lower DC in the right precuneus; (b) children with ASD + ADHD presented higher DC in the right calcarine and left superior frontal gyrus (SFG) compared with ASD only; (c) children with ASD + both displayed higher DC in the right calcarine and lower centrality in the right middle occipital gyrus compared with ASD only; and (d) across all children with ASD, there was a positive correlation between DC of the right calcarine with nonverbal behavior scores, and DC of the left SFG was negatively correlated with social scores. Our findings suggest that the right calcarine, left SFG, and default mode network nodes play important roles in the co‐occurrence of anxiety and ADHD among children with ASD. Autism Res 2019, 12: 1057–1068 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: The co‐occurrence of anxiety and attention‐deficit/hyperactivity disorder (ADHD) has been shown to influence the brain function of children with ASD. In order to gain a better understanding of this, the present study compared degree centrality, the amount of effective brain functional connectivity that reflects the characteristics of brain networks, among four groups: ASD only, ASD + anxiety, ASD + ADHD, and ASD + both anxiety and ADHD. We found that some areas located in the language processing network and primary visual cortex were associated with the co‐occurrence of ADHD, and some other areas located in the default mode network were associated with the co‐occurrence of both anxiety and ADHD. These findings provide more knowledge about the neural basis underlying behavioral changes related to the co‐occurrence of anxiety and ADHD in children with ASD.